2019
DOI: 10.1002/jor.24556
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Model of Periprosthetic Joint Infection in the Rat

Abstract: The majority of periprosthetic joint infections occur shortly after primary joint replacement (<3 months) and require the removal of all implant components for the treatment period (~4 months). A clinically relevant animal model of periprosthetic infection should, therefore, establish an infection with implant components in place. Here, we describe a joint replacement model in the rat with ultrahigh molecular weight polyethylene (UHMWPE) and titanium components inoculated at the time of surgery by methicillin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 43 publications
3
47
0
Order By: Relevance
“…Radiographs of tibia tumors were obtained by a Faxitron Portable X-Ray cabinet (Hewlett Packard, McMinnville, OR, USA), with imaging film (Portal Pack PPL-2, Merry X-Ray Corporation, San Diego, CA). The output voltage was 90 kVp and the exposure time was 7s [ 26 ]. Once the tumor became palpable, tumor sizes were measured by digital calipers and calculated by tumor volume = ½ × length × width 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Radiographs of tibia tumors were obtained by a Faxitron Portable X-Ray cabinet (Hewlett Packard, McMinnville, OR, USA), with imaging film (Portal Pack PPL-2, Merry X-Ray Corporation, San Diego, CA). The output voltage was 90 kVp and the exposure time was 7s [ 26 ]. Once the tumor became palpable, tumor sizes were measured by digital calipers and calculated by tumor volume = ½ × length × width 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Red arrows indicate the presence of septic loosening, and arrowheads indicate peri‐implant radiolucency. Adapted from Fan et al 51 [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Models Of Injury + Infectionmentioning
confidence: 99%
“…This dose was chosen based on previous models to create a chronic localized infection but to avoid systemic sepsis. 36 Additionally, a previous study found that inflammation due to surgery can persist until the 21-day time point, so this time point was chosen for tissue collection to optimize the measurement of infection-specific inflammatory cytokine responses. 36 Body temperature was monitored throughout the 21-day time period for the presence of fever to ensure no systemic sepsis occurred.…”
Section: Experimental Rat Model Of Localized Infectionmentioning
confidence: 99%
“…36 Additionally, a previous study found that inflammation due to surgery can persist until the 21-day time point, so this time point was chosen for tissue collection to optimize the measurement of infection-specific inflammatory cytokine responses. 36 Body temperature was monitored throughout the 21-day time period for the presence of fever to ensure no systemic sepsis occurred. For all groups, the exposed joint was closed with 3-0 vicryl (Ethicon, Inc.) and staples, then Vetbond tissue adhesive (3M) was applied externally.…”
Section: Experimental Rat Model Of Localized Infectionmentioning
confidence: 99%
See 1 more Smart Citation